Regulatory effect of glutathione on treg/Th17 cell balance in allergic rhinitis patients through inhibiting intracellular autophagy. (2nd January 2021) - Fan, Yuqin; Yang, Chenchen; Zhou, Jieyu; Cheng, Xuefeng; Dong, Yu; Wang, Qin; Wang, Zhentao
Abstract: Background: Glutathione is a potential therapy for systemic lupus erythematosus, but its role in allergic rhinitis (AR) has not been determined. This report probed into the actions of glutathione in AR, so as to supplement evidence for a therapeutical countermeasure for AR. Methods: In this study, peripheral blood mononuclear cells (PBMCs) of patients were extracted and processed with glutathione. PBMCs and nasal mucosa tissues were collected from AR mouse models treated with or without glutathione. The proportions of Th17/Treg cell markers and autophagy-related molecules in the nasal mucosa, PBMCs or Th17/Treg cells were assessed by quantitative real-time polymerase chain reaction (qRT-PCR), Western blot (WB) or flow cytometry analysis, and serum contents of related factors were analyzed by enzyme-linked immunosorbent assay (ELISA). Hematoxylin-eosin (HE) staining was applied to observe the thickness of mouse mucosa. Results: IL-17A, RORγt, Beclin1 and LC3-II/LC3-I levels were increased in AR patients, while Foxp3 and P62 were decreased. The serum contents of IL-17A and eosinophil cationic protein (ECP) in AR patients were elevated, but IL-10 level was reduced. In PBMCs of AR patients, the levels of IL-17A and LC3-II were increased, and the levels of Foxp3 and P62 were decreased, while these changes could be reversed by glutathione. In AR mouse models, glutathione could balance Th17/Treg cells, reduce autophagy, correct the levels of related cytokines in mouse serum, and shrunk mucosa thickness. Conclusion: Glutathione could rescue the imbalance of Treg/Th17 cells by suppressing intracellular autophagy, which might be beneficial to the treatment of AR patients.